The Influence of Leadership Style and Work Environment on Employee Performance in Jatimulya Village, South Tambun District - Muhammad Ikhsan; Ari Sulistyowati; Christoporus Indra Wahyu (Draf Solusi Indonesia, 2023)
The Influence of Leadership Style and Work Environment on Employee Performance in Jatimulya Village, South Tambun District. This research examines the influence of leadership style and work environment on employee performance in the Jatimulya sub-district, South Tambun District. The data obtained is primary data and the results of questionnaire answers were distributed to 53 respondents and processed using the SPSS (statistical product and serve solution) version 22 program. The results showed that in the partial t-test, the Leadership Style variable has a positive effect on Employee Performance and the Work Environment Variable has a positive effect on Employee Performance. In the simultaneous F test, the variables of Leadership Style and Work Environment together Influence Employee Performance